A new Malthinus (Coleoptera: Cantharidae: Malthininae) adds to the unrivaled diversity of arthropods found in Eocene Baltic amber - Pankowski, Madeline V. (Zootaxa, 2024)
A new species of soldier beetle (Cantharidae) from Eocene Baltic amber, Malthinus fabriziofantii sp. nov., is described and illustrated. This is yet one more species of Cantharidae documented from the Baltic deposit, a rich accumulation of amber that provides an unparalleled view of Eocene arthropods with more than 3,000 species discovered to date. Creating this remarkable deposit was a favorable blend of environmental elements that included a humid, warm climate; an assortment of different habitats; and conifer trees exuding profuse amounts of resin that trapped hundreds of thousands of insects, arachnids, and other small organisms that would become amber inclusions.